Developing and validating measurement for manufacturing flexibility implementation strategies: The PLS-SEM approach - Mohd Ghazali, Maarof; Gusman, Nawanir; Muhammad Fakhrul, Yusuf (Society of Cultural Studies and Social Sciences, 2023)
Manufacturing flexibility (MF) has been acknowledged as tool to help manufacturers adapting to uncertainty in the business environment. Fluctuating market demand, rapid technological changes, shorter product life cycles and increase level of customization are among the caused that create uncertainties in the market. However, manufacturers are facing great challenge to reap the real benefit from implementing manufacturing flexibility. Therefore, this study aimed to investigate the contributing factors that can enhance manufacturing flexibility implementation in mass customization production strategy among manufacturing firms in Malaysia. An extensive review on manufacturing flexibility literature and content validity assessment were conducted with industry practitioners and academicians. Four MF constructs and 16 measurement items have been identified from the review. A complete set of questionnaires have been developed by adopting, adapting, or self-develop based on the extensive literature review. This research study has recognized reliable MF constructs, consisting of four MF constructs and 16 measurement items. Thus, this study can be used to help identify provide method to enhance MF implementation at the manufacturing firm’s level. This study provided a useful tool for researchers to gain a greater knowledge and understanding on MF implementation. It acts to bridge the inadequacy of related studies on manufacturing flexibility by using the T-O-E framework. For practitioners, it is useful to review back the effectiveness of the usage of their internal resources in overcoming uncertainties in the environmental factors. More significantly, practitioners should be able to adopt the MF practices in a more holistic way. This study is among the first attempt to develop MF constructs for evaluating the enhancement of MF implementation in Malaysia.